Efficacy of video educational program on interception of urinary tract infection and neurological stress among teenage girls: An uncontrolled experimental study - Usha Rani Kandula; Daisy Philip; Sunitha Mathew; Anusha Subin; Godphy AA; Nidhi Alex; Renju B (Neuroscience Informatics, 2022)
Background: Nowadays, there is a lot more emphasis on promoting health, wellbeing, and self-care including stress management strategies. Health is regarded as a natural extension of a wellness-oriented lifestyle. The objectives are to measure knowledge, evaluate the efficacy of a video education program, and examine the relationship between before and after-existing knowledge measurement and specified socio factors on Urinary tract infections (UTI) and neurological stress in teenage girls.Materials and methods: This study employed an uncontrolled experimental study design. Initially, the mean and standard deviation of before and after-existing knowledge were determined. The ‘t’ test was applied to compare the variance between the before-existing and after-existing knowledge measurements of teenage girls on UTI and neurological stress, to find the efficacy of a video education program on eliminating urinary tract infection and neurological stress in teenage girls. Finally, the Chi-square model is used to measure the relationship between before-existing knowledge measurements and social characteristics.Results and interpretation: The analyzed data found that the teenage girls' mean after-existing knowledge measurement was 33.46% times greater than their mean before-existing knowledge measurement of 24.6%. According to the findings, there is no strong relationship between teenage girls before-existing knowledge measurement and selected socio-demographic factors.Conclusion: According to the study's findings, there is a critical need for healthcare providers to educate teenage girls about the interception of UTI prevalence and neurological stress management strategies inorder to avoid UTI among teenage girls.